Exploring the process of turning back to professional nursing practice in Iran: A grounded theory - Nooredin Mohammadi; Naiemeh Seyedfatemi; Alireza Nikbakht Nasrabadi; Mokhtar Mahmoudi (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: The current nursing shortage is complicated because of turnover intention among nurses. Most of the inactive nurses returned to professional nursing practice. Returned to professional nursing practice program was low attrition rates and a more cost-effective strategy that prepared inactive nurses returning to practice. This study aimed to explain the process of returned to professional nursing practice. MATERIALS AND METHODS: This study was a grounded theory study, which lasted from about 2018 to 2020. Data were collected through semi-structured interviews and observations with participants after signing an informed consent form. The average interview duration was 45 min. The study participants were selected through purposeful sampling from both public and private hospitals affiliated to Iran University of Medical Sciences. Interviews were verbatim transcribed and analyzed using a constant comparative analysis method. RESULTS: In this study, 16 participants were selected, including ten nurses, two educational supervisors, two head nurses, and two matrons. The "transformed competence" as the core concept and the four main concepts of "feeling alienated with the new environment," "getting prepared for restart," "gradual maturity in clinical practice," and "components of organizational culture" were extracted from the data analysis process. CONCLUSION: The process of returned to professional nursing practice in the context of the organizational culture of incentive learning leading to a high level of competence, and in the context of the organizational culture of inhibiting learning, is leading to deficiency incompetence.